Moradia e segregaÇao na cidade de Sao Paulo - Pasternak, Suzana; Machado Bogus, Lucia Maria (Universidad del Rosario, 2010)
The article aims to show striking of the socio- spatial inequalities city of São Paulo: at one extreme, the favelas and at the other extreme, the gated condominums.